ASSESSMENT OF TIME MANAGEMENT SKILLS AMONG NURSES WORKING IN THE EMERGENCY DEPARTMENT - PERVEEN , R; ASHIQ , A; FAROOQ , Z; PARVEEN , I; MUNIR , S; SEHAR , S; NAEEM , M (Biological and Clinical Sciences Research Journal, 2023)
Nursing is a noble profession; time management is paramount to ensure the best patient care, effective management, quality education, and personal responsibilities. This study aimed to assess the time management skills of nurses working in the emergency department. A quantitative cross-sectional descriptive study design was used to assess the time management skills of nurses in the emergency department. The study was conducted at Lahore General Hospital (LGH) and Sir Ganga Ram Hospital Lahore, using purposive sampling techniques. Nurses aged over 25, working in emergency departments, having clinical experience of 3-5 years, and being registered by the Pakistan Nursing Council were included. Non-cooperative nurses and those working in departments other than emergencies were excluded. Data was collected through questionnaires that had two parts. Part I included biographic data, and Part II comprised 15 questions about time management skills. The results showed that over 50% of the nurses working in the emergency department, considered a hectic hospital unit, possessed time management skills. These skills included confidence, competence, prioritizing tasks, command and control, planning tasks or daily activities, learning from mistakes, feeling confident and competent, and writing appointments, following schedules, and rewarding themselves for their good job. The study concluded that most nurses working in the emergency department possess time management skills necessary for effective patient care. It is recommended that hospitals should provide training and resources to enhance these skills and that further research should be conducted to explore other factors that may affect time management in this setting. Overall, improving time management skills can lead to better patient outcomes, increased job satisfaction, and reduced stress for nursing staff.